THE GRAMMATICAL STRUCTURE OF GERMAN SENTENCES AND THEIR TYPES. (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2024)
This article examines the grammatical structure of German sentences, focusing on their unique characteristics and types. German grammar is known for its complexity, particularly in sentence construction due to word order, case system, and verb placement. This study explores the fundamental principles of German sentence structure, including simple, compound, and complex sentence types. The research also highlights how these structures affect meaning and coherence, providing examples for clarification. Additionally, the article compares German sentence structures with English for better contextual understanding.